Multi-scale simulation of temperature on braided fibers reinforced composite plate considering the fluctuations. (June 2021) - Tu, Zecan; Li, Longkai; Mao, Junkui; Zhao, Chenwei; Wu, Xinyu
Highlights: Temperature distributions of braided FRC plate were simulated, considering the temperature fluctuations due to braided structure. Temperature fluctuations on braided FRC plate were obtained and described using Fourier series. Multi-scale thermal analysis method was built based on the homogenized model of whole plate and the single periodic braided structure. Abstract: The direct simulation based on the braided model of a whole fibers reinforced composite (FRC) component puts forward too high request on the calculating ability. So a multi-scale simulating method of the temperature on braided FRC plate is built in this paper, considering the temperature fluctuations of braided structures. The effective model of braided plate and the periodic braided structure are built, to obtain the homogenized temperature field and the fluctuations of temperature, respectively. The Fourier series is applied to build the functions of temperature fluctuations. Then the reconstructed temperature field of braided FRC plate could be obtained based on the homogenized temperature field and the functions of temperature fluctuations. Finally, the temperature field with fluctuations based on the braided model of whole plate is also simulated and compared with the reconstructed temperature field, to validate the accuracy of multi-scale thermal analysis method. Additionally, the experiment of temperature test on the braided FRC plate is also carried out to validate the accuracy of simulation, which presented good accuracy. The results show that, the temperature distribution of the braided FRC plate has significant fluctuating characteristics, the temperature in the region with braided yarns is relatively lower comparing with that in the matrix region, and the distributions of fluctuations are highly similar to the braided structures. The homogenized model based on the effective thermal conductivities could not obtain the temperature fluctuations of braided FRC plate. The maximum temperature difference between the braided model and the homogenized model reaches 25.37 K. Finally the maximum relative variation between the reconstructed temperature distribution and the temperature distribution based on the braided model is 3.18%, so the multi-scale thermal analysis method in this paper has good accuracy in simulating the temperature distribution of braided FRC plate with fluctuations.